Exploring the relationship between job quality and firm productivity in the manufacturing sector: Panel data evidence from Ethiopia - Tigabu Degu Getahun; Gebeyehu Manie Fetene; Heike Baumüller; Zaneta Kubik (University of Bonn, Center for Development Research (ZEF), 2024)
By leveraging firm-level panel data from 400 agro-processing and leather manufacturing firms in Ethiopia, this paper investigates links between firm productivity and monetary and non-monetary dimensions of job quality. The results point to a positive impact of higher salaries on firm productivity, but limited effects of non-monetary job quality indicators. Specifically, a 10% increase on each of the salaries of tenured medium- and high-skilled workers increase sales per worker by 1.79% and 1.46%, respectively, ceteris paribus. Similarly, increasing the starting salary of medium-skilled workers by 10% increases profit per worker, sales per worker and value-add per worker by 2.27%, 2.43% and 2.44%, respectively. Non-monetary job quality indicators had a weak impact on productivity, however, reducing the incentive of employers to invest in job quality improvements. Impact of productivity increases on monetary and non-monetary job quality indicators follow a similar pattern. An increase in profit per worker was found to increase the salaries of both tenured employees and new hires. For instance, a 10% increase in profit per worker increases tenured salaries of low-and medium-skilled workers by 0.2% and 0.3%, respectively, and starting salaries for low, medium and high-skilled workers by 0.21%, 0.28% and 0.27%, respectively. However, a statistically significant impact of profit per worker and value add per worker on non-monetary aspects of job quality was not.
Keywords: D24; E24; J24; 330; productivity; salary; job quality; labour compensation; firm performance